Experimental analysis of the exergetic performance of a solar air heater using separate liquid and solid sensible thermal storage media - Harikrishnan M; R Ajith Kumar; Rajesh Baby; Dani Percy; S. Ajith Kumar (Case Studies in Thermal Engineering)
This experimental research examines the exergetic performance of a solar air heater utilizing liquid and solid sensible thermal storage (SES) mediums separately. The primary objective is to evaluate and compare the thermal and exergetic efficiencies of both storage mediums under varying operational conditions. Three models are studied: (i) SAHRR: A solar air heater without any sensible energy storage (SES) medium, (ii)SAHRR-WPBS: A solar air heater incorporating pebbles as the SES medium, (iii)SAHRR-WTH55: A solar air heater incorporating Therminol 55 as the SES medium. The studies were carried out by employing an indoor solar simulator with different mass flow rates of 0.01, 0.02,0.03 and 0.06 kg/s with solar insolation varying between 600 and 1000 W/m2. By introducing SES mediums into the solar air heaters (SAHRR-WPBS.SAHRR-WTH55), the absorber plate's temperature was significantly lowered in comparison to the SAHRR, demonstrating the SES medium's thermal storage capabilities. For every mass flow rate taken into consideration, it was found that SAHRR-WPBS and SAHRR-WTH55 had more exergy efficiency than SAHRR. The outlet air temperature of SAHRR-WPBS and SAHRR-WTH55 stayed above the ambient temperature for 150 and 180 min, respectively, after operating for 2 h at 1000 W/m2 with a flow rate of 0.01 kg/s, following which the solar simulator was switched off. This proves that both SAHRR-WPBS and SAHRR-WTH55 can extend functioning for period more than 2.5 h after sunset. The designed SAHRR-WPBS and SAHRR-WTH55 can generate hot air in the range between 45- 65°C with minimal temperature variation over extended periods, making it suitable for producing high-quality dried products.